2010
DOI: 10.1172/jci40267
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory feedback loop involving p63 and IRF6 links the pathogenesis of 2 genetically different human ectodermal dysplasias

Abstract: The human congenital syndromes ectrodactyly ectodermal dysplasia-cleft lip/palate syndrome, ankyloblepharon ectodermal dysplasia clefting, and split-hand/foot malformation are all characterized by ectodermal dysplasia, limb malformations, and cleft lip/palate. These phenotypic features are a result of an imbalance between the proliferation and differentiation of precursor cells during development of ectoderm-derived structures. Mutations in the p63 and interferon regulatory factor 6 (IRF6) genes have been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
183
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(210 citation statements)
references
References 30 publications
22
183
4
Order By: Relevance
“…38 This increase in IRF6 may then lead to p63 degradation in keratinocytes, thereby restricting the proliferative potential and promoting keratinocyte differentiation. 39 Our data do not exclude that under certain conditions an interplay between IRF6 and p63 directly enhances RIPK4 promoter activity.…”
Section: G H and I)contrasting
confidence: 66%
“…38 This increase in IRF6 may then lead to p63 degradation in keratinocytes, thereby restricting the proliferative potential and promoting keratinocyte differentiation. 39 Our data do not exclude that under certain conditions an interplay between IRF6 and p63 directly enhances RIPK4 promoter activity.…”
Section: G H and I)contrasting
confidence: 66%
“…N1ICD binds to the IRF6 gene in keratinocytes and activates its expression (33). In turn, IRF6 promotes proteasomal degradation of p63 (30). An analogous mechanism could regulate p63 in vCTBs, because IRF6 rapidly increased after N1ICD expression.…”
Section: Discussionmentioning
confidence: 99%
“…S8). In addition, N1ICD increased expression of IFN regulatory factor 6 (IRF6), a negative regulator of p63 (30) (Fig. 5 D and F and SI Appendix, Fig.…”
Section: Ectopic Notch1 Induces An Extravillous Trophoblast Progenitomentioning
confidence: 99%
“…We found that p21 expression was restored in E14. Previous studies have demonstrated that IRF6 induces degradation of the p63 isoform ∆Np63 and that this is linked with the pathogenesis of VWS and PPS (Moretti et al, 2010;Thomason et al, 2010). In addition, ∆Np63 represses transcription of p21 in vitro and in vivo (Laurikkala et al, 2006;Welsh and O'Brien, 2009;Westfall et al, 2003).…”
Section: Irf6 Regulates Mee Disappearance Via P21 Expressionmentioning
confidence: 95%
“…Among the genes that have been associated with NSCL/P, IRF6 has been implicated in the largest percentage of cases (Koillinen et al, 2005;Srichomthong et al, 2005). Mutation of IRF6 can lead to the autosomal-dominant conditions VWS and PPS, which are characterized by oral clefting and lower lip pits (Kondo et al, 2002;Moretti et al, 2010). VWS and PPS are allelic variants of the same condition caused by different mutations of the same gene.…”
Section: Introductionmentioning
confidence: 99%